2015
DOI: 10.1007/s13277-015-3235-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between AT1 and AT2 angiotensin II receptor expression with cell proliferation and angiogenesis in operable breast cancer

Abstract: Angiotensin II (ANGII) has been associated with vascular proliferation in tumor and non-tumor models through its receptors AT1 and AT2. Our objective was to determine AT1 and AT2 receptor expression in operable breast cancer and its association with tumor grade, vascular density, and cellular proliferation. Seventy-seven surgically malignant breast tumors with no distant metastasis were included, and 7 benign lesions were used as controls. AT1 and AT2 receptor expression was determined by RT-PCR and immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 44 publications
2
37
0
1
Order By: Relevance
“…Recent study reported that AT1 expression was associated with enhance angiogenesis and cellular proliferation rate, but no relationship was found with AT2 in breast cancer [8]. Consistent with these results, in the present study, we found increased expression of AT1 and decreased expression of AT2 in HCC cells and tissues.…”
Section: Discussionsupporting
confidence: 89%
“…Recent study reported that AT1 expression was associated with enhance angiogenesis and cellular proliferation rate, but no relationship was found with AT2 in breast cancer [8]. Consistent with these results, in the present study, we found increased expression of AT1 and decreased expression of AT2 in HCC cells and tissues.…”
Section: Discussionsupporting
confidence: 89%
“…Since 1999, it has been reported that a decrease in the cell proliferation fraction has a predictive value with respect to the recurrence rate . Ki67 has been used as a marker of such proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that angiotensin II receptors, AT1 receptors and AT2 receptors are involved in enhancing tissue vascular endothelial growth factor protein levels, angiogenesis and tumor growth [29,30]. In addition, AT1 receptors are abundantly expressed in malignant neoplasms, including various types of lung cancer [31][32][33][34]. Fujita et al revealed that blocking angiotensin II receptors could reduce tumor growth and metastasis [35].…”
Section: Discussionmentioning
confidence: 99%